Effects of Adding Alcohols, Electrolytes and Carboxyl Methyl Cellulose (CMC) on Design Parameters in Internal Loop Airlift Bubble Column - Ali, Abdul Rahman; Najmuldeen, Ghazi Faisal (IJESRT, 2013)
The effect of gas velocity, liquid-phase properties, solid-particle concentration and the static liquid height on gas hold-up (ɛg) and mass transfer coefficient (KLa) were studied in a three phase internal loop airlift bubble column (ILBC) (the ratio of the draft tube to column diameter equal to 0.5). Air was used as a gas phase. Water and seven aqueous solutions of 10% concentration methanol, ethanol, NaCL, acetic acid, 50% glycerol and 2%CMC were used as the liquid phase. Polyethylene-non-porous-solid particles with a concentration of (50,100) Kg/m3 were used as solid phase. Superficial gas velocity varied from 0.01 m/s to 0.1 m/s and air dispersed into the center of the draught tube by using a porous gas distributor. The results showed that (εg) and (KLa) increase with increasing gas velocity and decrease with increasing solid particle concentration, static liquid height, viscosity and surface tension of liquid-phase.